Elucidation of Surface Functional Groups Deposited by Electrochemical Surface Treatment of Discontinuous Carbon Fiber by NEXAFS and XPS - Kolodziejczyk, Alec (Langmuir : the ACS journal of surfaces and colloids, 2023)
Control of carbon fiber heteroatom (oxygen and nitrogen) functionalization using electrochemical oxidation is explored in a variety of electrolyte solutions. Results of X-ray photoelectron spectroscopy (XPS) and near-edge X-ray absorption fine structure (NEXAFS) spectroscopy indicate that most electrolytes in aqueous and anodic conditions are limited to heteroatom surface content of no more than 13 atomic percent (at %) with a majority C-O and/or C-N moieties; the remaining moieties include an oxidative sequence of carbon (alcohol to ketone to carboxylate) and more complex O- and N-containing groups. The pH of the electrolyte solution was found to be crucial in controlling the ratio of the amount of oxygen to nitrogen functionalities, with the increased basicity of solution resulting in higher nitrogen deposition. The oxidative (and/or thermal) decomposition of many electrolytes during electrochemical treatment can have a major impact on functionalization through changes to pH. Oxidation of carbon fiber in some electrolyte solutions showed higher surface concentrations of heteroatoms (25-30 at %) than most electrolytes (13 at %). Mechanisms were proposed to explain how some electrolytes can exceed 13 at % of heteroatom deposition. Specifically, we hypothesized that electrolytes that contain organic ions with chelation capabilities and moieties that produce additional sites of functionalization can overcome that threshold